Pentingnya Peran Layanan Konseling Bagi Pasien di Rumah Sakit: ` - Widia Febriani; Melinda Yuliyani; ,Wim Febrian S; Dino Danuarta; Wahyu Samudra; Affan Yusra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
In writing this article, we discuss the importance of the role of counseling services for patients in hospitals. In writing this article, the author uses the literature review method, namely by collecting relevant data and then analyzing it to become the source of the articles made by the author. In the treatment process, it is undeniable that patients can feel hopeless with what they are experiencing, even they can think that the pain they are experiencing is the end of their life. With their psychic conditions that will hinder their recovery process, so that psychological support and guidance so that they remain mentally stable and can help make the recovery process faster. So it can be seen that the role of the counselor to provide services to patients is very necessary to be able to work collaboratively with other hospital personnel